Identification of genetic loci conferring seed coat color based on a high-density map in soybean - Yuan, Baoqi; Yuan, Cuiping; Wang, Yumin; Liu, Xiaodong; Qi, Guangxun; Wang, Yingnan; Dong, Lingchao; Zhao, Hongkun; Li, Yuqiu; Dong, Yingshan (Frontiers in Plant Science, 2022)
Seed coat color is a typical evolutionary trait. Identification of the genetic loci that control seed coat color during the domestication of wild soybean could clarify the genetic variations between cultivated and wild soybean. We used 276 F10 recombinant inbred lines from the cross between a cultivated soybean (JY47) and a wild soybean (ZYD00321) as the materials to identify the quantitative trait loci (QTLs) for seed coat color. We constructed a high-density genetic map using re-sequencing technology. The average distance between adjacent markers was 0.31 cM on this map, comprising 9083 bin markers. We identified two stable QTLs (qSC08 and qSC11) for seed coat color using this map, which respectively explained 21.933% and 26.934% of the phenotypic variation. Two candidate genes (CHS3C and CHS4A) in qSC08 were identified according to the parental re-sequencing data and gene function annotations. Five genes (LOC100786658, LOC100801691, LOC100806824, LOC100795475 and LOC100787559) were predicted in the novel QTL qSC11, which, according to gene function annotations, might control seed coat color. This result could facilitate the identification of beneficial genes from wild soybean and provide useful information to clarify the genetic variations for seed coat color in cultivated and wild soybean.